Architectural Bionics in the Creation of New Uzbekistan - Yakubova Khilola Bakhtiyarovna (Genius Journals, 2023)
Independent Uzbekistan made a big leap in the development of architecture and urban planning in a short period of time. Today, the foundation of the great state architecture of the future is being laid, and the republic has great economic, scientific, technical and creative power. The new Uzbekistan has the power to build architecturally biconical buildings that will give a new image to Uzbekistan
Keywords: the responsibility of architects is growing exponentially; unusual architectural forms; architecture; foundations